Saturday
March 25, 2017

Post a New Question

Posted by on .

I find from the first equation that x = 3y and plugging in to the second equation we get
o.2y+37(-3y)=23
0.2y-111y=23
-110.8y=23
y=-23/110.8
x=69/110.8
need help to understand why the elimination process in not work in this linear equation?

  • math116 - ,

    without both equations, I do not have a clue either.

  • math116 - ,

    12y +4x=0
    0.2y+37x=23
    does this help

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question